The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0227155
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative computed tomography imaging for dose calculation in intraoperative electron radiation therapy: Initial clinical observations

Abstract: In intraoperative electron radiation therapy (IOERT) the energy of the electron beam is selected under the conventional assumption of water-equivalent tissues at the applicator end. However, the treatment field can deviate from the theoretic flat irradiation surface, thus altering dose profiles. This patient-based study explored the feasibility of acquiring intraoperative computed tomography (CT) studies for calculating three-dimensional dose distributions with two factors not included in the conventional assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This study revealed that by adjusting the intensity of the scan beam, IMET can be achieved with nonuniform dose distributions according to the intraoperative images such as the CT image ( 34 ) and the three-dimensional ultrasound images ( 35 ). The electron beam is collimated by the applicator, which determines the scan beam size.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that by adjusting the intensity of the scan beam, IMET can be achieved with nonuniform dose distributions according to the intraoperative images such as the CT image ( 34 ) and the three-dimensional ultrasound images ( 35 ). The electron beam is collimated by the applicator, which determines the scan beam size.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intraoperative volumetric real-time imaging to evaluate applicator placement and optimize the treatment plan is only feasible if an imaging device that can calculate density relative to water, such as computed tomography (CT), O-arm cone beam CT (CBCT), and C-arms CBCT [5,6], is available in the operating room (OR) [7,8]. Other systems are under development to enhance the accuracy of the dose administered in IORT treatments [9].…”
Section: Introductionmentioning
confidence: 99%
“…The time is probably ripe for a change. Availability of accurate dose calculation algorithms for clinical use, such as real-time Monte Carlo calculation [ 4 , 5 , 6 ], the prospected coming of radically new irradiation schemes such as FLASH therapy [ 7 ], and the possibility to use in-room imaging [ 8 ] call for an evolution of treatment planning systems in IORT.…”
Section: Introductionmentioning
confidence: 99%